Landsdown Crescent - Palmer, John
With the success of the Royal Crescent, many similar projects were completed-at Buxton in Derbyshire, in London, and here at Lansdown Crescent in Bath. Perhaps only in England, at this time of national and personal freedom, could such schemes have emerged. In effect, the needs of the individual, of households, of towns and cities alike were satisfied in one architectural whole. Lansdown Crescent hugs the contours of the south-facing slopes of Lansdown Hill, making a sinuous whole of return crescents on a convex plan. Indeed, it marks the high of Georgian elegance.